UPAYA MENINGKATKAN DISIPLIN SISWA DENGAN KEGIATAN EKSTRAKURIKULER KEPRAMUKAAN - Sakri Sakri (MEDIA DIDAKTIKA, 2020)
The relationship between the activities of scouting education with student discipline is a container or vehicle for education in the form of a game as well as the implementation of an education in an extracurricular activity, especially scouting while discipline is an attitude that is obedient and follow rules. The purpose of this study was to determine whether there is influence of scouting education to discipline students in grade V and VI Elementary School Gintungan I. In this study the authors use data analysis deemed appropriate and simple in its processing by using statistical analysis product moment correlation. Based on the analysis of the study showed that there was no significant influence of scouting education with student discipline, because t value of -2.288 smaller 5% level of 2.048, the null hypothesis (Ho) is rejected, which means there is no significant effect. This is due to scouting activities just an extracurricular activity that is less than optimal implementation. Besides scouting activities is not a favorite choice in this school because there are other activities that drum band.